2019
DOI: 10.1123/jsr.2017-0173
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Salted Ice Bag Versus Cryocompression on Decreasing Intramuscular and Skin Temperature

Abstract: Salted IB with elastic wrap compression, GR, and PP-ice produced equivalent intramuscular temperature decreases during the treatment period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
1
15
1
1
Order By: Relevance
“…However, skin temperature is highly variable and is further influenced by the presence of a barrier and the addition of external compression. Correlations in this study as well as previous studies 12,19,27 have demonstrated no correlation between skin and muscle temperatures, indicating that skin temperatures cannot be utilized to approximate muscle temperature decreases.…”
Section: Discussionsupporting
(Expert classified)
See 2 more Smart Citations
“…However, skin temperature is highly variable and is further influenced by the presence of a barrier and the addition of external compression. Correlations in this study as well as previous studies 12,19,27 have demonstrated no correlation between skin and muscle temperatures, indicating that skin temperatures cannot be utilized to approximate muscle temperature decreases.…”
Section: Discussionsupporting
(Expert classified)
“…Previous research using the PP-ice indicates it is capable of producing equivalent intramuscular temperature decreases as salted ice bags and GameReady. 19 Skin temperatures using PP-ice were 5C lower that PP-gel by minute 12, and 10.5C lower by the end of the 30 minute treatment ( Table 2). In our study, the PowerPlay with gel pack decreased skin temperature only 4C during a 30-minute treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this was determined using an ice bag not wrapped around the gastrocnemius and temperature measured 2 cm into the muscle. In other research, 22 a salted ice bag with elastic wrap, GameReady ice bag, and PowerPlay ice bag decreased intramuscular temperatures similarly over a 30-minute intervention. Even though subcutaneous tissue thickness was measured in both studies, treatment times were not altered.…”
Section: Discussionmentioning
confidence: 78%
“…One text 11 even went so far as to recommend treatment times. A number of researchers [13][14][15][16][17][18][19][20][21][22][23][24] have incorporated cooling recommendations based on subcutaneous tissue thickness into their study designs or accounted for subcutaneous tissue thickness in different results across patients. Textbooks and scholarly articles suggested translating these recommendations to patient care, but many clinicians were complacent and relied on a ''cookbook approach'' to patient care.…”
mentioning
confidence: 99%